Enhanced thermoelectric properties of binary CoSb3 by embedding FeCl3-intercalated graphene nanosheets. Issue 13 (October 2021) - Zong, Peng-an; Mao, Zhengdong; Ou, Yixiang; Shi, Taifeng; Wang, Zhiweng; Zhang, Qihao; Zhang, Peng; Wan, Chunlei
Highlights: FeCl3 -intercalated graphene nanolayers were introduced into grain boundaries of CoSb3 . The carrier concentration and mobility were increased. The lattice thermal conductivity was effectively suppressed due to interfacial scattering. zT of 0.6 was achieved, comparable to that of commercially used filled p-type Fe3 CoSb12 . Abstract: Filling the icosahedral lattice holes of the cage-compound CoSb3 with alkali, alkaline-earth and rare-earth metal atoms can endow CoSb3 with the transport characteristic of "phonon-glass-electron-crystal". However, the filler atoms greatly increase the cost in raw material as well as fabrication complexity. In this work, we embedded FeCl3 -intercalated graphene nanolayers into polycrystalline CoSb3 by a solution-dispersion method combined with spark plasma sintering technology. The graphene nanosheets were mainly distributed in grain boundaries. Due to the increased carrier concentration and mobility, the electrical conductivity was improved. Meanwhile, due to the enhanced interfacial phonon scattering, the lattice thermal conductivity was effectively suppressed. The thermoelectric figure of merit of the nanocomposite reached 0.6 at a mass content of 0.2 % FeCl3 -intercalated graphene nanolayers, outperforming all reported values of binary CoSb3 based nanocomposites, and even comparable to that of commercially used filled p-type Fe3 CoSb12 . This work provides a promising strategy for low-cost fabrication of p-type skutterudites.